KEHADIRAN PERTAMBANGAN KOBALT DI REPUBLIK DEMOKRATIK KONGO TERHADAP PENERAPAN HAK ASASI MANUSIA PENAMBANG ARTISANAL DI ERA PEMERINTAHAN FÉLIX TSHISEKEDI - Jesica Millenia (2022)
This study aims to see how the experience of cobalt mining in the Democratic Republic of the Congo affected the implementation of the human rights of artisanal miners in the Félix Tshisekedi era from the point of view of International Relations. Research falls into the focus of human rights studies and exploitation through the study of international cobalt mining in the Democratic Republic of the Congo. The method used in this research is the descriptive qualitative method. The researcher uses data collection techniques in library research, document collection, and internet-based research. Researcher use the concept of Human Rights and International Labor Standards on Human Rights to form a general picture of the flow of thought to produce answers and research findings. Results Based on the data analysis conducted by the author, it is known that during the Félix Tshisekedi era, human rights violations still occurred. Especially for artisanal miners. These miners are increasingly exploited due to increased demand for cobalt, countries that make laws that relieve multinational companies, companies that use the services of artisanal miners, and militant groups that force these artisanal miners to work. Of the nine exploitation criteria, seven exploitation criteria based on the ILO International Labor Standards have occurred during the reign of Félix Tshisekedi, namely, bad living conditions, excessive working days or hours, hazardous work, low or no salary, no access to education, deplorable working conditions, and wages manipulation.